Click-functionalized hydrogel design for mechanobiology investigations. Issue 9 (2nd August 2021) - Hui, Erica; Sumey, Jenna L.; Caliari, Steven R.
Abstract : This review article covers the use of click chemistries toward the design of dynamic and instructive hydrogels for understanding cell mechanobiology. Abstract : The advancement of click-functionalized hydrogels in recent years has coincided with rapid growth in the fields of mechanobiology, tissue engineering, and regenerative medicine. Click chemistries represent a group of reactions that possess high reactivity and specificity, are cytocompatible, and generally proceed under physiologic conditions. Most notably, the high level of tunability afforded by these reactions enables the design of user-controlled and tissue-mimicking hydrogels in which the influence of important physical and biochemical cues on normal and aberrant cellular behaviors can be independently assessed. Several critical tissue properties, including stiffness, viscoelasticity, and biomolecule presentation, are known to regulate cell mechanobiology in the context of development, wound repair, and disease. However, many questions still remain about how the individual and combined effects of these instructive properties regulate the cellular and molecular mechanisms governing physiologic and pathologic processes. In this review, we discuss several click chemistries that have been adopted to design dynamic and instructive hydrogels for mechanobiology investigations. We also chart a path forward for how click hydrogels can help reveal important insights about complex tissue microenvironments.